Lipidome remodeling activities of DPA-EA in palmitic acid-stimulated HepG2 cells and the in vivo anti-obesity effect of the DPA-EA and DHA-EA mixture prepared from algae oil - Fang, Hua; Cao, Yin; Zhang, Jianyu; Wang, Xiumei; Li, Mengyu; Hong, Zhuan; Wu, Zhen; Fang, Meijuan (Frontiers in Pharmacology, 2023)
The orphan nuclear receptor Nur77 is a potent druggable target for inflammatory diseases. It has been confirmed to play a critical role in controlling inflammatory responses and show a protective function in obesity. Obesity is associated with chronic low-grade inflammation and marked imbalances in lipid metabolism. Recently, we have reported ω-3 PUFA-EA derivatives (DPA-EA and DHA-EA et al.) as a series of new Nur77-targeting anti-inflammatory agents. Herein, we aimed to evaluate the lipid-lowing effect and the underlying mechanism of DPA-EA using lipidomics, with another Nur77-targeting anti-inflammatory compound Celastrol as a reference. Besides, we examined the anti-obesity effect of the DPA-EA and DHA-EA mixture synthesized from algae oil in a high-fat diet (HFD)-fed mice model. The results showed DPA-EA significantly alleviated lipid accumulation with lower toxicity than Celastrol. DPA-EA and Celastrol as Nur77-targeting compounds simultaneously reduced 14 lipids (9 TGs, 2 PCs, 1 PA, 1 SM, and 1 LacCer) and increased 13 lipids (4 DGs, 6 LPEs, 2 PEs, and 1PC) in Pal-stimulated HepG2 cells. However, Cer lipids were more sensitive to DPA-EA, while the over-downregulation of SM lipids might be associated with the off-target toxicity of Celastrol. Finally, it was demonstrated that the mixture of DPA-EA and DHA-EA synthesized from algae oil significantly decreased TG, TC, and LDL levels and increased HDL levels in HFD-fed mice, exerting an excellent anti-obesity effect. Together, Nur77-targeting anti-inflammatory compound DAP-EA could promote the hydrolysis of PEs and TGs to ameliorate lipid accumulation, and the DPA-EA and DHA-EA mixture prepared from algae oil might be a potential therapeutic agent for obesity and other inflammation-related diseases.